Nitrogen addition regulates the effects of variation in precipitation patterns on plant biomass formation and allocation in a Leymus chinensis grassland of northeast China - Ren, Jianli; Wang, Chengliang; Wang, Qiaoxin; Song, Wenzheng; Sun, Wei (Frontiers in Plant Science, 2024)
Global warming is predicted to change precipitation amount and reduce precipitation frequency, which may alter grassland primary productivity and biomass allocation, especially when interact with other global change factors, such as nitrogen deposition.The interactive effects of changes in precipitation amount and nitrogen addition on productivity and biomass allocation are extensively studied; however, how these effects may be regulated by the predicted reduction in precipitation frequency remain largely unknown. Using a mesocosm experiment, we investigated responses of primary productivity and biomass allocation to the manipulated changes in precipitation amount (PA: 150 mm, 300 mm, 450 mm), precipitation frequency (PF: medium and low), and nitrogen addition (NA: 0 and 10 g N m -2 yr -1 ) in a Leymus chinensis grassland. We detected significant effects of the PA, PF and NA treatments on both aboveground biomass (AGB) and belowground biomass (BGB); but the interactive effects were only significant between the PA and NA on AGB. Both AGB and BGB increased with an increment in precipitation amount and nitrogen addition; the reduction in PF decreased AGB, but increased BGB. For root to shoot ratio, significant effects were detected in the PA, PF and interactions among the PA, PF and NA. In addition to influence on BGB, the PA, PF treatments also affected the ratio of 0-10 cm BGB to total BGB whereas the low PF treatment induced an increase in the allocation of BGB to 0-10 cm soil layer. The reduced PF treatment induced an enhancement in the variation of soil moisture, which subsequently affected photosynthesis and biomass formation. Overall, there were mismatches in the aboveand belowground biomass responses to changes in precipitation regime. Our results suggest the predicted changes in precipitation regime, including precipitation amount and frequency, is likely to alter primary productivity and biomass allocation, especially when interact with nitrogen deposition. Therefore, predicting the influence of global changes on grassland structure and functions requires the consideration of interactions among multiple global change factors.